High Frequency of Symptoms Suggestive of Endometriosis in a Clinic‐Based Sample of Low‐Income Women in Mexico City. Issue 4 (21st November 2018) - Harris, Courtney; Willie, Tiara C.; Cardoso, Lauren F.; Campos Rivera, Paola A.; Diaz Olavarrieta, Claudia; Pollack, Anna Z.; Gupta, Jhumka
Abstract : Endometriosis affects an estimated 10 percent of women and girls globally, yet little is known about symptoms and awareness among women in low‐ and middle‐income countries. This commentary presents a descriptive secondary analysis of baseline data from a clinic‐based intervention study with low‐income women in Mexico City who experienced intimate partner violence in the past year (N = 754). The secondary analysis examined symptoms that may be suggestive of endometriosis as well as endometriosis awareness. Over half of participants reported at least one symptom suggestive of endometriosis (59.3 percent), while 12.5 percent of those reporting a symptom had ever heard of the disease. Pain‐related symptoms were classified as pain with menses disrupting household chores, pain with menses disrupting work or social gatherings, and/or pelvic pain outside of menses disrupting daily activities. Fewer women who reported pain‐related symptoms had heard of the disease compared to those who reported a history of infertility (11.4 vs. 15.7 percent, respectively). This study documents levels of awareness of endometriosis among women in Mexico City and underscores the importance of integrating endometriosis education into broader global reproductive health agendas.